Astrocyte activation in hindlimb somatosensory cortex contributes to electroacupuncture analgesia in acid-induced pain - Ye, Qing; Li, Jie; Ren, Wen-Jing; Zhang, Ying; Wang, Tao; Rubini, Patrizia; Yin, Hai-Yan; Illes, Peter; Tang, Yong (Frontiers in Neurology, 2024)
Background Several studies have confirmed the direct relationship between extracellular acidification and the occurrence of pain. As an effective pain management approach, the mechanism of electroacupuncture (EA) treatment of acidification-induced pain is not fully understood. The purpose of this study was to assess the analgesic effect of EA in this type of pain and to explore the underlying mechanism(s). Methods We used plantar injection of the acidified phosphate-buffered saline (PBS; pH 6.0) to trigger thermal hyperalgesia in male Sprague–Dawley (SD) rats aged 6–8 weeks. The value of thermal withdrawal latency (TWL) was quantified after applying EA stimulation to the ST36 acupoint and/or chemogenetic control of astrocytes in the hindlimb somatosensory cortex. Results Both EA and chemogenetic astrocyte activation suppressed the acid-induced thermal hyperalgesia in the rat paw, whereas inhibition of astrocyte activation did not influence the hyperalgesia. At the same time, EA-induced analgesia was blocked by chemogenetic inhibition of astrocytes. Conclusion The present results suggest that EA-activated astrocytes in the hindlimb somatosensory cortex exert an analgesic effect on acid-induced pain, although these astrocytes might only moderately regulate acid-induced pain in the absence of EA. Our results imply a novel mode of action of astrocytes involved in EA analgesia.